2002
DOI: 10.1044/1092-4388(2002/037)
|View full text |Cite
|
Sign up to set email alerts
|

Botox Treatment in Adductor Spasmodic Dysphonia

Abstract: Over the years many studies have been conducted to document the treatment effects of Botulinum toxin type A in adductor spasmodic dysphonia. The results of these studies have led to the view that overall Botulinum toxin treatment is moderately effective. This study reviews efficacy research qualitatively and quantitatively to determine the extent to which this conclusion is fully supported by the data. Although the data indicate moderate overall improvement as a result of Botulinum toxin treatment, they also s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0
9

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(74 citation statements)
references
References 37 publications
1
61
0
9
Order By: Relevance
“…Seven BoNT serotypes are known to exist (A-G), all of which are produced by strains of the bacterium Clostridium botulinum. BoNT causes the paralytic syndrome botulism, but also holds therapeutic application in the treatment of dystonias [3][4][5][6], spasticity [7,8], facial rhytides [9], axillary hyperhidrosis [10,11], and some pain syndromes [12,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seven BoNT serotypes are known to exist (A-G), all of which are produced by strains of the bacterium Clostridium botulinum. BoNT causes the paralytic syndrome botulism, but also holds therapeutic application in the treatment of dystonias [3][4][5][6], spasticity [7,8], facial rhytides [9], axillary hyperhidrosis [10,11], and some pain syndromes [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…This form of treatment is successful in alleviating voice symptoms temporarily [3]; however, as a peripheral (and symptom) based treatment for a central nervous system disorder, it does not provide a cure. Therefore, BoNT therapy must be readministered periodically.…”
Section: Introductionmentioning
confidence: 99%
“…For spasmodic dysphonia (SD), there is data from several clinical studies and meta-analyses [Wong et al 1995;Brin et al 1998;Whurr et al 1998;Finnegan et al 1999;Boutsen et al 1998;Watts et al 2006Watts et al , 2008Blitzer, 2010]. One double-blind, placebo-controlled study examined the effects of BoNT-A versus saline in 13 adductor SD patients and revealed significant effects of BoNT-A on voice quality, perceived voice improvement and acoustic measurements [Troung et al 1991].…”
Section: Spasmodic Dysphoniamentioning
confidence: 99%
“…O uso de TB é considerado o tratamento mais utilizado para a DLAD (Ludlow et al, 1988;Aronson et al, 1993;Adams et al, 1995;Woodson, 1995;Wong et al, 1995a;Inagi et al, 1996;Lindestad et al, 1997;Zwirner et al, 1997;Finnegan et al, 1999;Ludlow, 2000;Galardi et al, 2001;Langeveld et al, 2001;Boutsen et al, 2002;Tish et al, 2003;Adler et al, 2004;Cannito et al, 2004;Blitzer, 2005;Wingate et al, 2005;Baylor et al, 2007;Cannito et al, 2008;Ludlow et al, 2008;Paniello et al, 2009;Blitzer, 2010;Elmiyeh et al, 2010;Novakovic et al, 2011;Fulmer et al, 2011;Cannito et al, 2012ab;Dejonckere et al, 2012;Gama et al, 2012;Damrose, 2012;Hu et al, 2013;Rosow et al, 2013), sendo aplicado, principalmente, no músculo TA, apresentando alívio dos síntomas no segundo ou terceiro dia. Após a ação do medicamento, o tratamento atinge a estabilidade após duas semanas, quando se percebe melhora na qualidade da voz (Ludlow et al, 1988;Boutsen et al, 2002;Blitzer, 2010;Cannito et al, 2012a). Embora os principais estudos apresentem a aplicação da TB no músculo TA como método de escolha, existe referência na literatura da aplicação nos músculos TA e CAL (Inagi et al, 1996)...…”
Section: Discussionunclassified
“…Os indivíduos que que recebem a injeção de TB relatam presença de picos de fraqueza muscular entre o segundo e terceiro dia após o procedimento, diminuindo na segunda semana, obtendo ótima função vocal (Ludlow et al, 1988;Boutsen et al, 2002;Meyer, 2012).…”
Section: Tratamento Com Toxina Botulínica Para Distonia Laríngea De Aunclassified